The hidden face of the information society: the environmental impact of production, consumption and technological waste - Tucho Fernández, Fernando (2017)
The information society is built upon an important technological ground. Its operation requires an IT infrastructure that has been growing during the last decades. In parallel, climate change looms over the future of the planet as a disturbing threat, which demands a social and political response. The widespread perception about technology considers that its environmental impact is scarce. This paper discusses this perception, completing for this purpose a bibliographical review about the negative effects that technological production, consumption and waste produce on the environment in which our societies are developed: this issue has received scant attention to date from the Academe.